Influência das relações de poder na implementação do planejamento estratégico - Ribeiro, José Orion Martins (2013)
The Strategic Planning tool is widely known in the management of the most varied types of organizations, being these private or public. However, in its second phase, the implementation has not obtained the expected success. As stated by Kaplan and Norton (2001), only 10% of the formulated strategies are successfully implemented, what makes evident that the large bottleneck of Strategic Planning is found in its implementation phase. This tool is, in essence, a change process and so should be treated since it could result in the necessity of changes in the organizational structure, in internal processes, in the way of conducting formal and informal interpersonal relations in the organization. Due to these possible changes, to begin a strategic planning process, a good formulation of strategies and an effective strategic implementation is necessary in order to reverse the situation presented by Kaplan and Norton. Aware of this fact and as a way to strengthen the Strategic Planning implementation, the aspects related to the relation of power in the organizations, organizational culture and evaluation should be taken into account, because in the same way that these aspects are influenced by the process of changes, they influence the strategic decisions. This study aims to identify and report the aspects that involve the relations of power and that influence in the implementation of Strategic Planning. To achieve the proposed objective, a case study methodology of qualitative nature and of exploratory and descriptive character was used. Based on the bibliographical data found, a diagnosis model of the relation of power in the organizations was developed and was composed of four dimensions: contextual power, personal power, managing power and leading power. To test the model, a semi-structured interview was applied to four pro-rectors and five teaching unit directors of the Federal University of Santa Maria. Data was collected and analyzed, and the results obtained showed that the aspects related to the relations of power compose an important variable of study when the implementation of a change process, such as the strategic planning in a successful way is intended. The model demonstrated how the studied unit is more focused on the power of position and on bureaucratic managing.